Tantangan Pendidikan Islam Di Era Society 5.0 - Muslikh, Muslikh (Universitas Majalengka, 2024)
Society 5.0 is a challenge for Islamic education that must be addressed wisely to achieve its goal of developing the personality of people who are faithful and devoted to Allah SWT, and can apply their knowledge for the benefit of the people. This research explains Islamic Education's efforts to face Society 5.0. This research is a literature study using qualitative-descriptive-analytic methods. data collection through study of primary and secondary sources from books, texts, journals or articles. Data analysis was carried out through exploration of Islamic Education and Society 5.0. The research results show: (1) Islamic education must be able to solve various problems, produce students who think critically and creatively; (2) The need for reconstruction and reorientation of Islamic Education to achieve educational goals through improving the quality of human resources, completeness of technology-based facilities and infrastructure, and innovative learning models; (3) Futuristic Islamic education and digital-based learning as a means of enriching information and accelerating the achievement of alearning goals for students.